Fenomenologi Konten Kreator Dalam Mengedukasi Masyarakat Melalui Media Sosial Tiktok - Zhazaretta, Ananda; Djuhardi, Lidia (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
TikTok social media has become an important platform for content creators to disseminate various information, including education for the community. Related to the dissemination of educational information, this study aims to find out the experiences and motivations of content creators in presenting educational content on Tik Tok media, as well as how they interpret it. The research approach is qualitative with a phenomenological study, to explore the experiences, motivations and meanings of content creators in educating the public on TikTok. Through the analysis of qualitative data from in-depth interviews and observations with several education-focused content creators, this study identifies essential patterns in the experiences and the ways content creators make meaning of them. The informants are purposively selected content creators who have experience in their field, especially in educational content. The results of the study reveal that some of the informants’ experiences in creating and presenting their content are very interesting because they involve the emotional content of the creators and the audience. This is also supported by their motivation in providing educational information. Meanwhile, the meaning of education through TikTok media for content creators is that TikTok is seen as an effective tool for conveying information in a creative way and is able to attract the attention of a wider audience. The implications of these findings explain a deeper understanding of the role of TikTok content creators in educating, where Tik Tok is not only considered a medium of entertainment, but also beneficial for society, especially in educating the public.